A case of human infection with a novel Babesia species in China. Issue 1 (December 2016) - Man, Su-Qin; Qiao, Ke; Cui, Jie; Feng, Meng; Fu, Yong-Feng; Cheng, Xun-Jia
Abstract Background Babesiosis is an uncommon but emerging tick-borne disease caused by the genusBabesia . In this case study, we report a case of human infection with a novelBabesia sp. in China. Findings The patient in question had been suffering from repetitive occurrences of mild fever of unknown origin and fatigue for 10 years. Ring forms, tetrads, and one or two dots of chromatin or trophozoite-like organisms were observed in the patient's thin blood smears and bone marrow smears. Using a confocal laser-scanning microscope, it was observed that the patient's serum had reactivity with the surface proteins of theB. microti strain. Electron microscopy revealed oval red blood cells with 1 ~ 2 μm of knob protrusions in the cellular membrane. The results of theBabesia -specific nested PCR assay for 18S rRNA confirmed the presence ofBabesia infection. The construction of a phylogenetic relationship showed clustering withB. microti andB. duncani, which was identified as a novelBabesia species and named asBabesia sp. XXB/HangZhou. Azithromycin, doxycycline, and moxifloxacin hydrochloride were shown to relieve symptoms but were not as effective after continuous usage. After atovaquone (Mepron®) administration, the patient recovered from fever and tested negative for detection ofBabesia -specific genes. Conclusion Babesia sp. XXB/HangZhou is a novelBabesia species, which causes mild babesiosis in an immunocompetent patient.